PENGARUH ISLAMIC LEADERSHIP DAN ISLAMIC ORGANIZATIONAL CULTURE TERHADAP EMPLOYEE PERFORMANCE DENGAN VARIABEL INTERVENING JOB SATISFACTION (BANK SYARIAH INDONESIA KANTOR AREA JEMBER): (THE INFLUENCE OF ISLAMIC LEADERSHIP AND ISLAMIC ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION INTERVENING VARIABLES (BANK SYARIAH INDONESIA JEMBER AREA OFFICE)) - Andini, Azizah Noer; Hardinawati, Lusiana Ulfa (UPT Penerbitan Universitas Jember, 2024)
This study aims to analyze the impact of Islamic leadership and Islamic organizational culture on employee performance, with job satisfaction as a mediating variable, at Bank Syariah Indonesia in the Jember Area Office. This research employs a quantitative method with a survey approach, using a questionnaire as the instrument. The sample consists of 41 employees working as tellers, customer service representatives, and backoffice staff. The sample was selected using purposive sampling techniques. The data were analyzed using SEM-PLS techniques. The research findings indicate that Islamic leadership has a positive and significant effect on job satisfaction, Islamic leadership has a positive and significant effect on employee performance, Islamic organizational culture does not affect job satisfaction, Islamic organizational culture does not affect employee performance, job satisfaction has a positive and significant effect on employee performance, job satisfaction does not mediate the effect of Islamic organizational culture on employee performance, and job satisfaction does mediate the effect of Islamic leadership on employee performance.